2016
DOI: 10.1097/gme.0000000000000578
|View full text |Cite
|
Sign up to set email alerts
|

The association between recent abuse and menopausal symptom bother

Abstract: In the present study from the Data Registry on Experiences of Aging, Menopause, and Sexuality, menopausal symptom bother scores were directly associated with recent self-reported abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…To our knowledge, the association between lifetime IPV or sexual assault and menopause symptoms has not been previously examined. However, evidence from the Study of Women’s Health Across the Nation suggests a similar association between childhood abuse and hot flashes, while smaller studies of women seeking menopause-related care suggest that IPV in the past year is associated with general menopause symptoms and poor sleep among women in midlife …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the association between lifetime IPV or sexual assault and menopause symptoms has not been previously examined. However, evidence from the Study of Women’s Health Across the Nation suggests a similar association between childhood abuse and hot flashes, while smaller studies of women seeking menopause-related care suggest that IPV in the past year is associated with general menopause symptoms and poor sleep among women in midlife …”
Section: Discussionmentioning
confidence: 99%
“… 35 Finally, a study showed an association between recent abuse and the severity of menopausal symptoms. 27 …”
Section: Discussionmentioning
confidence: 99%
“…5-10 Moreover, many factors can impact both sleep and sexual function such as general health, age, emotional and psychological issues, life events/changes contributing to stress, social support or lack thereof, recent abuse, medications and chronic disease. 11-19 For example, data from the Study of Women's Health Across the Nation (SWAN) demonstrated a co-occurrence of a triad of menopausal symptoms including sleep disturbance, depressed mood and sexual problems. 20 …”
Section: Introductionmentioning
confidence: 99%